The role of institutions in the migration of corporate governance practice into emerging economies: The case of Africa - Bruce Hearn; Lars Oxelheim; Trond Randøy (Research Institute of Industrial Economics (IFN), 2016)
This study examines the role of the institutional environment in influencing the migration of corporate governance best practice into 22 emerging African economies. Using a unique and comprehensive sample hand-collected sample of 202 IPO firms from across the continent, we adopt a novel institutional logics perspective in studying the diffusion of CEO salary disclosure - a central element of corporate transparency. Our findings reveal that the adoption of CEO salary disclosure by firms is more likely in more homogenous informal institutional contexts. Complementarities arising from disclosure originating from an Anglo-American shareholder value governance framework and indigenous formal institutions adhering to English common law infer disclosure is more likely than in contrasting civil code law contexts. Finally, firms with higher proportions of their boards of directors being drawn from indigenous social elites are less likely to disclose CEO salary - where this is reversed in the context of elevated institutional quality. Our findings are important for regulatory authorities, investors and policy makers alike who are involved in institutional improvements in emerging economies.
Keywords: G23; G38; M12; M14; M16; 330; Disclosure; CEO Salary; Institutional Theory; Africa; Emerging Economies; IPO